Traditional uses, phytochemistry, pharmacology activity and plant tissue culture of ficus carica l. (a mini review) - Fahrauk Faramayuda; Sigid Pamungkas Wicaksono; Akhirul Kahfi Syam; Soraya Riyanti; Ari Sri Windyaswari; Yeni Karlina; Elfahmi Elfahmi (Riset Informasi Kesehatan, 2022)
Ficus carica L. or Figs plants are plants originating from the Middle East and the Mediterranean region, which then spread to various parts of the world through explorers who try to plant in various countries. Figs plants can grow in various habitats, including infertile rocky soils, forests, shrubs, and even hot dry soils. Figs plants have several varieties that can be distinguished from the shape of the stem, the shape of the leaves, and the fruit's color. Figs plants are widely used as traditional medicine for both leaves and fruit. Noted in several countries have used the Figs plant as one of the plants used for traditional medicine. Figs plants are widely used for antioxidants, anticancer, hepatoprotective, antidiabetic, antibacterial, antipyretic, antituberculosis, antispasmodic antiplatelet in several countries. Figs plants contain secondary metabolites of alkaloids, latexonins, phenols, and flavonoids. There is one method of multiplication of Figs plants that began to be widely used, namely plant tissue culture. Plant tissue culture is a method of propagation using tissue slices or parts of plants that are small and in aseptic conditions. Several studies have been obtained to trace figs plants by tissue culture methods using slices of leaves and shoots.